ANALISIS KUALITAS BUTIR SOAL ULANGAN HARIAN SEKOLAH DASAR MATA PELAJARAN BAHASA INDONESIA MENGGUNAKAN RASCH MODEL - Anastya Nida Alhana; Syahrul Ramadhan (Universitas Nahdlatul Ulama Al Ghazali Cilacap, 2024)
This research aims to examine and explain the characteristics of Indonesian language test questions for fourth-grade students at SD Islam Plus Masyitoh Kroya using the Rasch model. This study is a descriptive research based on quantitative methods. The population of this study consists of fourth-grade students at SD Islam Plus Masyitoh Kroya. The sample was selected using stratified proportional random sampling method, with a sample size of 20 students. The data used in this study are responses from the final exam in Indonesian language, which consists of 20 multiple-choice questions. Data collection and analysis in this research were conducted using the winstep application with the Rasch model approach. The findings of this study indicate that there are 2 questions that do not meet the criteria in the MNSQ assessment, which are question number 5 with a value of 4.95 and question number 12 with a value of 5.36. This indicates that both questions exceed the set limits. However, overall these questions are consistent with the model or model fit because they meet one of the criteria for model fit. The question with the highest difficulty level is question number 5 with a difficulty index of 2.10, while the question with the lowest difficulty level is question number 7 with a difficulty index of -2.10. This analysis indicates that 18 question items meet the criteria for good difficulty level, while 2 question items in question number 5 and 7 are categorized as less good because they exceed the difficulty index of 2.10 and -2.10.